2018
DOI: 10.3892/ol.2018.8581
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of the miR‑148a‑associated mechanisms of metastasis in non‑small cell lung cancer

Abstract: MicroRNAs (miRs) are small non-coding RNAs that regulate gene expression and protein synthesis. Our previous study demonstrated that miR-148a suppressed the metastasis of non-small cell lung cancer (NSCLC) and. However, the modulatory mechanism of this effect remains unclear. In the present study, quantitative proteomic technology was used to study the protein expression profile of SPC-A-1 cells subsequent to the downregulation of miR-148a expression, in order to elucidate the molecular mechanism of the suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…MiR-148a is a member of miR-148/152 family and its dysregulatiuon has been observed in several human cancers [15][16][17]. In this study, we found that the expression of miR-148a was significantly down-regulated in OSCC tissues and cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…MiR-148a is a member of miR-148/152 family and its dysregulatiuon has been observed in several human cancers [15][16][17]. In this study, we found that the expression of miR-148a was significantly down-regulated in OSCC tissues and cells.…”
Section: Discussionmentioning
confidence: 48%
“…MiRNA-148a (MiR-148a) belongs to miR-148/miR-152 family which is characterized by a stem-loop structure [14]. The abnormal expression of miR-148a has been observed in several human cancers, including gastric cancer [15], esophageal squamous cell carcinoma [16], non-small cell lung cancer [17] etc. The function of miR-148a in OSCC was also reported in published articles.…”
Section: Introductionmentioning
confidence: 99%
“…6). For example, two highlighted miRNAs, hsa-mir-7a and hsa-mir-155, play important roles in both lung cancer 27,28 and asthma, 29,30 which are involved in multiple meta-paths in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan–Meier analysis revealed that seven miRNAs (miR-148a, miR-196a, miR-1246, miR-338-3p, miR-150, miR-645 and miR-342-5p) were closely related with the prognosis of glioma patients. miR-148a has been found to be abnormally expressed in diverse malignant tumors, such as colorectal cancer ( Tsai et al, 2019 ), ovarian cancer ( Zhu et al, 2019 ), hepatocellular carcinoma ( Babu & Muckenthaler, 2019 ), breast cancer ( Lacerda et al, 2019 ), esophageal cancer ( Wang et al, 2019 ), gastric cancer ( Song et al, 2018 ), non-small cell lung cancer ( Chu et al, 2018 ) and glioma ( Cai, Zhu & Gong, 2018 ; Cui et al, 2017 ). In addition, Cai, Zhu & Gong (2018) found that miR-148a regulated STAT3 pathway activity by directly targeting CADM1 to promote glioma cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%